The Clash of Muslims and the State: Waqf and Zakat in Post Independence Indonesia - Jahar, Asep Saepudin (Studia Islamika, 2006)
Law no. 38/1999 on zakat administration was able to be successfully enacted not solely because the roots of democracy had began to grow in the country; but also because this law is based on the rationale purpose of zakat, that is, to help the poor. In this article, furthermore, the state is responsible to protect and provide necessary support for the poor and needy citizens, even though in fact, the state fails to do so, This is of course of great relevance considering the main aim of zakat is to improve the social and economic position of the poor.DOI: 10.15408/sdi.v13i3.556